REPRESENTASI GAYA HIDUP SEHAT DALAM WEB SERIES “SORE” - Chelsea Maulia; Nadya Ishma Ashila; Siggi Amalia Bertianto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
This research was conducted based on the phenomenon of delivering messages through the representation of a healthy lifestyle through the